Understanding Belonging and Community Connection for Seniors Living in the Suburbs - Jakubec, Sonya L. (2019)
While much has been explored about notions of both place and belonging in regard to community health of various populations, little is known of the phenomena specific to suburban dwelling seniors. More and more seniors are living in suburban neighborhoods, communities that do not tend well to the belonging needs of this population. This qualitative study sought the perspectives of suburban dwelling seniors about the role of belonging and community connection to their health and wellbeing. Informed by strengths-based approaches to community development and health, the study engaged people from three community groups of older adults in a Canadian suburb (a seniors’ recreational/social group, and two cultural groups) in group interviews concerning the topic. Discoveries included an understanding of belonging as both personal and social, and identification of facilitators and barriers to belonging at personal and systemic levels. Belonging was experienced through connection, contribution and cooperation. These findings are important to shape community engagement with seniors and to inform decision-making and program developments in areas of recreation, leisure, health services, community policing, city planning and other services.